Trade, Earnings, and Mobility - Swedish Evidence - Per-Anders Edin; Peter Fredriksson; Per Lundborg (Uppsala University, Department of Economics, 2000)
Using a large longitudinal data set, we study the effects of increased trade on earnings and mobility in the Swedish labor market in the late 1980s and early 1990s. Earnings respond significantly to changes in industry sales, whether generated by domestic market forces or international trade: Swedish exports (imports) raise (lower) annual earnings, but changes in trade affect earnings just as any other shift in market conditions. In general, the wage effects are small; the prime response to changes in the product market appears to be variations in employment. We also examine whether trade has differential effects across skill groups. However, we do not find systematic differences in the effects of trade across the earnings distribution.
urn:nbn:se:uu:diva-2508
Keywords: F14; J23; J31; J62; J63; 330; International trade; Earnings; Mobility; Außenhandel; Einkommenseffekt; Arbeitsmobilität; Verarbeitendes Gewerbe; Schweden